Pengaruh Moral Reasoning Dan Kompetensi Auditor Terhadap Kualitas Audit - Ni Wayan Suci Verani; Ni Ketut Muliati (UNHI Press, 2023)
Audit quality is the implementation of an audit carried out by an auditor based on established standards so and auditor can provide reports that can be accounted for to clients and have accurate evidence. This research was conducted to determine the influence of Moral Reasoning and Auditor Competence on Audit Quality. This research was conducted at Public Accounting Firms in Bali. The sample used in this study was 102 Auditors from 13 Public Accounting Firms. The data analysis technique uses Multiple Linear Regression Analysis consisting of F Test, Adjusted R² and Hopotesis Test (t Test) to test the influence of moral reasoning variables and auditor competence on audit quality. The results of the study stated that Moral Reasoning and Auditor Competence had a positive and significant effect on the quality of audits at Public Accounting Firms in Bali. This study proves that moral reasoning and auditor competence affect audit quality by 70.2% and the remaining 29.8% are influenced by other factors that are not raised in this study